Universal verification methodology-based airborne electronic hardware certification approach for ARINC-429 - Ayaz, Ibrahim; Sakarya, Ufuk; Hokelek, Ibrahim (EMERALD GROUP PUBLISHING LTD, 2023)
PurposeThe purpose of this paper is to present a verification methodology for custom micro coded components designed for Avionics projects. Every electronic hardware which will be developed for an aircraft must be designed with the compliance of DO-254 processes. Requirements are the key elements of the aviation. All the requirements must be covered by the design to be considered as completed. Therefore, verification of the custom micro coded components against requirements should be comprehensively addressed. The verification using the manual testing approach is less preferable, as humans can possibly make mistakes. Therefore, the most used verification method today is the automated simulation. Design/methodology/approachThe industry has developed a common methodology for generating automated testbenches by following the standardized guideline. This methodology is named as the universal verification methodology (UVM). In this paper, the verification study of ARINC-429 data bus digital design is presented to describe the DO-254 verification process using the UVM. FindingsThe results are supported with functional coverage and code coverage in addition to the assertions. It is observed that the design worked correctly. Originality/valueTo the best of the authors' knowledge, this is the first study comprehensively describing the DO-254 verification process and demonstrating it by the UVM application of ARINC-429 on programmable logic devices.
Keywords: DO-254; UVM; ARINC-429; Aviation; Certification; Engineering